Evaluation of sugarcane (Saccharum officinarum) germplasm for quality, yield traits and effects of flowering on cane traits - KHOKHAR, JASWANT S; JAMWAL, NAVDEEP S; SANGHERA, GULZAR S; SINGH, PARAMJIT (The Indian Journal of Agricultural Sciences, 2022)
Sugarcane (Saccharum officinarum L.) is an important commercial crop grown globally for its sugar-rich stalk. Low genetic variations and unwanted flowering in modern sugarcane varieties affect sugarcane quality and production. Therefore, a panel of 628 genetically diverse sugarcane clones were evaluated under field conditions at the Regional Research Station, Kapurthala, Punjab Agricultural University during 2019–20, for quality, yield and yield traits. The effect of flowering on quality and yield traits on a sub-set of 34 flowering sugarcane clones was also studied. A panel of 628 sugarcane clones showed greater genetic diversity for all the traits. HR brix per cent varied from 14–24%, number of millable cane (NMC) varied from 13–80 and single cane weight varied from 0.4–2.6 kg in 628 clones under field conditions. Non-flowering sugarcane clones’ mean performance was greater than flowering clones for most of the traits. However, no significant differences in quality traits among the clones at different flowering stages (flag leaf, tip emergence and complete flowering) were observed. Therefore, there is a huge genetic diversity in sugarcane germplasm for quality and yield traits and it should be exploited by breeding community for the development of sugarcane varieties with improved yield and better quality.